Two new species of Myxobolus (Myxozoa: Myxobolidae) infecting the gill and scales of the smallmouth bass, Micropterus dolomieu (Centrarchiformes: Centrarchidae) in the French Broad River Basin, North Carolina. (December 2022) - Ksepka, Steven P.; Rash, Jacob M.; Bullard, Stephen A.
Abstract: Two new species of Myxobolus Bütschli, 1882 (Bivalvulida: Myxobolidae) are described from the gill and scales of smallmouth bass ( Micropterus dolomieu Lacepède, 1802 [Centrarchiformes: Centrarchidae]) from the Watauga River, French Broad River Basin, North Carolina, United States. Myxobolus intralamina n. sp. infects the lumen of the lamellar arterioles and Myxobolus infrabractea n. sp. infects the inner surface of the scale. They differ from all congeners by a combination of myxospore dimensions, polar tubule coil count, and the presence or absence of an iodinophilic vacuole in the sporoplasm and an intercapsular process. A phylogenetic analysis of the small subunit ribosomal DNA (SSU rDNA) recovered M. intralamina n. sp. sister to Myxobolus lepomis and Myxobolus branchiarum and M. infrabractea n. sp. sister to Myxobolus micropterii in a clade composed of five Myxobolus spp. infecting centrarchids and Henneguya spp. (Myxobolidae) infecting percids. Histological sections of infected gill revealed intra-lamellar plasmodia of M. intralamina n. sp. within the lumen of the lamellar arterioles and plasmodia of M. infrabractea n. sp. developing beneath the scales. These new species comprise the first species of Myxobolus reported from a black bass ( Micropterus Lacepède, 1802) in the Southeast United States. Graphical abstract: Unlabelled Image Highlights: Two new species of Myxobolus from the gill and scales of smallmouth bass in North Carolina. First species of Myxobolus reported from black basses in SE United States. Histological assessment of infections by the new species. Phylogenetic analysis of related myxobolids.